Nrf2 target genes are induced under marginal selenium-deficiency - Müller, Mike (Springer-Verlag, 2010)
A suboptimal selenium supply appears to prevail in Europe. The current study, therefore, was focused on the changes in gene expression under a suboptimal selenium intake. Previous microarray analyses in the colon of mice fed either a selenium-adequate or a moderately deficient diet revealed a change in genes of several pathways. Severe selenium-deficiency has been found previously to influence Nrf2-regulated genes of the adaptive response. Since the previous pathway analyses were done with a program not searching for Nrf2 target genes, respective genes were manually selected and confirmed by qPCR. qPCR revealed an induction of phase II (Nqo1, Gsts, Sult1b1 and Ugt1a6) and antioxidant enzymes (Hmox1, Mt2, Prdx1, Srxn1, Sod1 and Gclc) under the selenium-poor diet, which is considered to compensate for the loss of selenoproteins. The strongest effects were observed in the duodenum where preferentially genes for antioxidant enzymes were up-regulated. These also include the mRNA of the selenoproteins TrxR1 and GPx2 that would enable their immediate translation upon selenium refeeding. The down-regulation of Gsk3β in moderate selenium-deficiency observed in the previous paper provides a possible explanation for the activation of the Nrf2 pathway, because inhibition of GSK3β results in the nuclear accumulation of Nrf2.